AB0134 Phosphorelated stat3 expression in peripheral blood mononuclear cells in rheumatoid arthritis. (12th June 2018) - Perniola, S.; Cacciapaglia, F.; Natuzzi, D.; Bizzoca, R.; Lacarpia, N.; Iannone, F.
Abstract : Background: The JAK-STAT pathway is mainly involved in the regulation of the expression of cytokines and growth factors; so it controls the proliferation, differentiation, migration and death of the cells of the immune system. In patients with RA, studies have shown increased activation of STAT3 with undergoes phosphorylated (pSTAT3), probably due to increased levels of cytokines such as IL-6, IL-11, IL-12. Objectives: This study aims at investigating the level of expression of STAT3 and pSTAT3 in peripheral blood lymphomonocytes cells of patients with Rheumatoid Arthritis (RA), correlating them with disease activity (ESR, CRP, clinimetric tests). Methods: Patients affected with RA, according to the 2010 EULAR/ACR classification criteria, were enrolled in this study. Exclusion criteria were: minority age, status of pregnancy or breastfeeding, concomitant any other autoimmune disease. At entry (new treatment with csDMARDs or biological drugs) ESR, CRP, DAS28-ESR, CDAI and peripheral venous blood sample were collected. The expression of STAT3 and pSTAT3 in lymphomonocytes cells, CD4 and CD14 cells were evaluated by flow-cytometry assay. The level of STAT3 gene was studied by qPCR. Differences for continuous variables were evaluated using the Mann-Whitney test, while for categorical data the Kolmogorov-Smirnov test. Correlations were assessed using the Spearman test. Results: Twenty RA patients were studied, comparing STAT3 and pSTAT3 levels with 9 seronegative arthritis patients (SA) and 8 healthy control (HC). While no difference in the expression of STAT3 levels between the 3 groups (in flow-cytometry and qPCR assays), pSTAT3 was higher in RA (9, 5%) than in SA (2, 74%) (p: 0.005) or HC (4, 81%) (p: 0.04); between the 3 groups, pSTAT3 was differently expressed in CD4-lymphocytes and CD14-monocytes (figure 1). We also demonstrated a correlation between pSTAT3 level in CD14 +cells and ESR (p: 0.026; r: 0, 4625). We found no correlation between pSTAT3 expression and Body Mass Index or disease duration. Conclusions: In this study, STAT3 seems to be activated more in RA than SA or HC. Monocytes (as macrophage) and T-cells have important role in RA. Isomaki et al. demonstrated a correlation between IL-6 level and STAT3 activation so it might be suggested a possible role of pSTAT3 as a biomarker of disease activity. However, further studies are needed to explore the important role of JAK-STAT pathway in RA. References: [1] Harris TJ, et al. Cutting Edge: An In Vivo Requirement for STAT3 Signaling in Th17 Development and Th17-Dependent Autoimmunity. J Immunol2007. [2] Nurieva R, et al. Generation of Inflammatory Helper T Cells STAT3 Regulates Cytokine-mediated. J. Biol. Chem. 2007. [3] Walker JG, Smith MD. The Jak-STAT Pathway in Rheumatoid Arthritis.Editorial of The Journal of Rheumatology 2005. Disclosure of Interest: None declared